Human Security in Carbon Footprint Calculator Program for the Development of Sustainable Tourism in Indonesia - Ulung, Alessandro Kurniawan; Abdurrohim, Muhammad; Saputro, Pradono Budi; Tarigan, Djoesept Harmat; Dwijayanti, Risqi Inayah; Ayu, Andina Mustika (Rumah Jurnal UNEJ, 2025)
This article aims to examine the Carbon Footprint Calculator (CFC) program carried out by the Indonesian government to realize sustainable tourism in Indonesia. The CFC program facilitates travelers to calculate the carbon emissions they produce during their trips. The calculation of the carbon footprint left by the travelers is then converted into the amount of money that they need to pay as their responsibility for polluting the environment. The CFC program will use the money to restore the environment through various carbon offset initiatives, such as the trees-planting initiative and eco-tourism development. To formulate the CFC program, the Indonesian government teamed up with a non-state actor, Jejak.in, which invented the technology of calculating carbon emissions. As such, this article seeks to describe how the CFC program operates in Indonesia and what causes explain the program. To that end, we employ a qualitative research method. This method allows us to combine interviews with a systematic literature review to explore the CFC program. Using the human security concept, we argue that the government rolled out the CFC program because carbon emissions generated in the tourism industry have posed a bigger threat to human security in the country, causing issues in environmental security, health security, and economic security. In the CFC program, the state actor not only expects the travelers to have a greater awareness of the carbon emission threat to the three securities above but also urges them to take responsibility for the emissions they produce and take part in realizing low carbon and sustainable tourist destinations. CFC works in a way that the government and Jejak.in utilize the website indonesia.travel to facilitate travelers to count and offset their carbon footprint.